ACCESS TO MATERNAL, CHILD, AND FAMILY PLANNING SERVICES AMONG PHILIPPINE CONDITIONAL CASH TRANSFER BENEFICIARIES IN A RURAL SETTING: A CROSS-SECTIONAL STUDY - Jeric Jamandre; Ceilo Kristine Calma; Maikko Cordero; Delsol Ann Dela Cruz; Randy Ian Gallego (Journal of Public Health Research and Community Health Development, 2026)
Background: Extreme poverty remains a persistent global challenge that limits access to essential services, including healthcare. In response, the Philippine government implemented the Pantawid Pamilyang Pilipino Program (4Ps), a conditional cash transfer initiative aimed at improving the well-being of impoverished households. However, empirical evidence on how the program influences healthcare access among beneficiaries in rural settings remains limited. Purpose: This study aimed to assess the accessibility of maternal and child health and family planning services among the 4Ps beneficiaries in a rural province of Zamboanga Sibugay, Philippines; and to generate empirical evidence to support improvements in public health and social protection policies affecting low-income households in resource-constrained communities. Methods: This cross-sectional study involved 90 program beneficiaries selected through purposive sampling. Data was collected using a validated and reliability-tested survey instrument. Descriptive statistics summarized sociodemographic data and perceptions of healthcare access, while Spearman’s rho correlation analysis examined relationships between respondents’ profiles and healthcare accessibility. Results: Maternal and child health and family planning services were generally accessible to beneficiaries. However, respondents reported that prescribed medicines unavailable in health centers were purchased out-of-pocket. No significant relationships were identified between most sociodemographic factors and healthcare access, except for a correlation between monthly income and access to family planning services (p < 0.05). Conclusion: Socioeconomic constraints, particularly income, continue to shape healthcare access among low-income families despite government assistance. The enhancement of program support mechanisms, particularly in medicine provision and reproductive health education, has the potential to augment the program's long-term public health impact.